The symbolism of light and its significance in sufism with special reference to the Mathnawi of Rumi - Azhani binti Ahmad (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research mainly studies the symbolism of light in Jalāl al-Dīn Rūmī's Mathnawī. The Mathnawī, which is a tour de force in the history of Muslim literature, presents Rūmī's sophisticated and lyrical interpretations of light. The textual analysis of 'light'-related metres opens up the possibility of comprehending the spirituality of light. The symbolism of light in the Mathnawī is greatly inspired by the Qur'an and the pinnacle would be the Verse of Light (Qur'an, al-Nūr: 35). This verse helps Muslims understand the concept of light as belonging to the realms of metaphysics and epistemology. It is a powerful verse which conjures up the image of Allah's Light, so much so that it has become mystically fascinating. Metaphorical analyses of this verse attempt to unlock the secrets (asrār) of Divine Light, layer by layer. This research finds that physical light has been used to symbolise transcendental light; the aforementioned verse is the ultimate instance. At this point, the symbolism of light serves a spiritual purpose, with which religious people search for assurance of faith. To some Muslim mystic-philosophers, such as, al-Ghazālī, Suhrawardī and Ibn ʻArabī, the symbolism of light became a platform to probe into the theological aspects of light and their relation to humans. Meanwhile, the symbolism of light in the Mathnawī depicts Rūmī's insightful reference to the manifestations and the significance of Divine Light in the lives of Muslims. Therefore, in Islam, the symbolism of light is none other than to provide tawhidic insights into “Allah is the Light of the heavens and the earth.”